Economics of land degradation Initiative: Methods and approach for global and national assessments - Ephraim Nkonya; Joachim von Braun; Alisher Mirzabaev; Quang Bao Le; Ho Young Kwon; Oliver Kirui (University of Bonn, Center for Development Research (ZEF), 2013)
Healthy land ecosystems are essential to sustainable development, including food security and improved livelihoods. Yet, their key services have usually been taken for granted and their true value underrated, leading to land degradation becoming a critical global problem. This pattern of undervaluation of lands is about to change in view of the rapidly rising land prices, which is the result of increasing shortage of land and high output prices. Despite the urgent need for preventing and reversing land degradation, the problem has yet to be appropriately addressed. Policy actions for sustainable land management are lacking, and a policy framework for action is missing. Such a framework for policy action needs to be supported by evidence-based and action-oriented research. The Economics of Land Degradation (ELD) initiative seeks to develop such a science basis for policy actions to address land degradation. The purpose of this methodological paper is to provide with sound and feasible standards for ELD assessment at global and national levels. Only if some basic standards are identified and adhered to, comparative assessments can be conducted between countries and useful aggregation of findings, based on these case studies, can be achieved. Therefore, using the Total Economic Value (TEV) framework, the paper identifies minimum core standards that need to be adhered to in all country case studies to generate comparable material for international assessment and ELD policy guidance. It also identifies additional and desirable areas of information and analyses that would add value to the country case study material. The proposed framework is also intended as a forward-looking agenda which can guide future research.
Keywords: B41; Q01; Q15; Q24; Q51; 330; economics of land degradation; ELD; case studies; total economic value